Rozkład przestrzenny cudzoziemców w Poznaniu - Gajda, Hanna (Człowiek i Społeczeństwo, 2014)
The presence of foreigners in Poland is yet a relatively unexplored phenomenon and an interesting research area. Since the political transformation and the Polish accession to the European Union, there has recently been an upward trend towards an increase of the population of immigrants (within the last couple of years). The vast majority of migration is into cities. Therefore, the activity of foreigners contributes both to the social and structural changes and raises several questions about their socio-spatial assimilation. This article aims to present the spatial distribution of foreigners in the city of Poznań. The article presents the results of research on patterns of the settlement of foreigners (temporary and permanent residence) in the city of Poznań from 1999 to 2011.